Measurement of the Cost-of-Living Index in the Easi Model: Evidence from the Japanese Expenditure Data - Ogura, Manami (Asian Journal of Economic Modelling, 2015)
In this study, I measure the change in the cost-of-living index in Japan over approximately 20 years using newly developed demand system model. I find that the cost-of-living index, itself, was shifted upward by price changes, despite the existence of a protracted deflation in Japan. This implies an increase in consumer surplus along with changes in consumer expenditures, prices, and demographics. Further, I find that the substitution effect in the cost-of-living index is so large that the increase in consumer surplus depends on it. That is, consumers substitute greatly for cross-price goods in the face of price changes.